Projection of diversity in Higher Education. A study of an institutional communication media in a Spanish university (Communication & Society, 2023)
The way in which diversity is conveyed through the media can reflect the attitude of the communicators themselves and contribute to shaping society’s attitudes towards diversity. The aim of the study was to identify how diversity is conveyed by the University to the Society. A content analysis of diversity-related news items in the University’s Institutional Newspaper Journal of the Pablo de Olavide University (DUPO) (626 news items out of 3,186 published between 2016 and 2019, a full rector’s term) was conducted. Heterogeneity in diversity was identified: gender, functional, cultural, sexual, religious and age, with gender and functional or disability diversity being predominant. Dissemination of diversity was linked to the fields of social sciences, humanities and sport. Communicators were government teams, with a slightly larger role for women. In conclusion, the institutional communication of diversity carried out from the most common official communication channel of the university analysed is the majority compared to the actions of professors and researchers, and a heterogeneous conception of diversity was found, linking it to issues of gender, inequalities and violence.